Adapting and sustaining operations in weak institutional environments: A business ecosystem assessment of a Chinese MNE in Central Africa - Parente, Ronaldo; Rong, Ke; Geleilate, José-Mauricio G.; Misati, Everlyne (Journal of International Business Studies, 2019)
Multinational enterprises (MNEs) sometimes pursue opportunities in largely uncharted, distinctive institutional environments. How do these firms sustain operations in such settings? We explore how MNEs tailor and maintain operations in institutionally weak, precarious, and challenging host-country environments, such as those devastated by conflicts. We draw on the business ecosystem framework and analyze a qualitative longitudinal case study of a Chinese state-owned MNE that entered and developed its operations in the Democratic Republic of Congo (DRC) in Central Africa. Our findings indicate that after entry, the MNE sustained its operations in the DRC by engaging in collective actions and coevolving with key stakeholders within its business ecosystem. These stakeholders included the home and host governments, state-owned enterprises, privately owned enterprises, and local communities. Our qualitative data further suggest that the MNE’s business ecosystem evolved through three stages—exploring, establishing, and embedding—and that within this ecosystem, the key stakeholders also coevolved with the MNE by adopting new roles over time.